Предмет: Математика,
автор: Аноним
3. Решите примеры по формуле: a-b-c=a- (b + c). 31-12-15 91-45-12 49-26-7 34-7-11 64-18-21 71-23-12
Ответы
Автор ответа:
14
1. 31 - 12 - 15 = 31 - (12 + 15) = 31 - 27 = 4
2. 91 - 45 - 12 = 91 - (45 + 12) = 91 - 57 = 34
3. 49 - 26 - 7 = 49 - (26 + 7) = 49 - 33 = 16
4. 34 - 7 - 11 = 34 - (7 + 11) = 34 - 18 = 16
5. 64 - 18 - 21 = 64 - (18 + 21) = 64 - 39 = 25
6. 71 - 23 - 12 = 71 - (23 + 12) = 71 - 35 = 36
2. 91 - 45 - 12 = 91 - (45 + 12) = 91 - 57 = 34
3. 49 - 26 - 7 = 49 - (26 + 7) = 49 - 33 = 16
4. 34 - 7 - 11 = 34 - (7 + 11) = 34 - 18 = 16
5. 64 - 18 - 21 = 64 - (18 + 21) = 64 - 39 = 25
6. 71 - 23 - 12 = 71 - (23 + 12) = 71 - 35 = 36
Похожие вопросы